The Effectiveness of Group Cognitive Behavioral Therapy on Psychological Flexibility and Psychological Hardiness in Female Heads of Household - Tahmasebi , Roghyeh; Jafarnejad Sani , Pegah; Sadeghi , Sepideh; Mosavi , Seyed Khadijeh; Moghaddasi, Roya Sadat (Psychology of Woman Journal, 2025)
Objective: The present study aimed to determine the effectiveness of group cognitive behavioral therapy (CBT) on psychological flexibility and psychological hardiness in female heads of household.Methods and Materials: This research employed a quasi-experimental design with a pretest-posttest setup, including an experimental group and a control group. The study population consisted of 140 female heads of household who referred to the Welfare Organization in Sari during the second half of 2023 and registered their cases. The sample included 30 female heads of household, selected using a non-random purposive sampling method and subsequently randomly assigned to either the experimental group (15 participants) or the control group (15 participants). Data collection was conducted using questionnaires on psychological flexibility and psychological hardiness. The experimental group underwent eight sessions of group CBT, each lasting 120 minutes. Following the completion of group CBT sessions, a posttest was administered to both the experimental and control groups.Findings: The findings indicated that the mean scores of psychological flexibility and psychological hardiness in the posttest for the experimental group were significantly higher compared to the pretest.Conclusion: Therefore, group CBT has a positive impact on psychological flexibility and psychological hardiness in female heads of household.